Clinical outcomes and risk factors for severe COVID‐19 in patients with haematological disorders receiving chemo‐ or immunotherapy. (12th August 2020) - Fox, Thomas A.; Troy‐Barnes, Ethan; Kirkwood, Amy A.; Chan, Wei Yee; Day, James W.; Chavda, Selina J.; Kumar, Emil A.; David, Kate; Tomkins, Oliver; Sanchez, Emilie; Scully, Marie; Khwaja, Asim; et al.
Summary: Haematology patients receiving chemo‐ or immunotherapy are considered to be at greater risk of COVID‐19‐related morbidity and mortality. We aimed to identify risk factors for COVID‐19 severity and assess outcomes in patients where COVID‐19 complicated the treatment of their haematological disorder. A retrospective cohort study was conducted in 55 patients with haematological disorders and COVID‐19, including 52 with malignancy, two with bone marrow failure and one immune‐mediated thrombotic thrombocytopenic purpura (TTP). COVID‐19 diagnosis coincided with a new diagnosis of a haematological malignancy in four patients. Among patients, 82% were on systemic anti‐cancer therapy (SACT) at the time of COVID‐19 diagnosis. Of hospitalised patients, 37% (19/51) died while all four outpatients recovered. Risk factors for severe disease or mortality were similar to those in other published cohorts. Raised C‐reactive protein at diagnosis predicted an aggressive clinical course. The majority of patients recovered from COVID‐19, despite receiving recent SACT. This suggests that SACT, where urgent, should be administered despite intercurrent COVID‐19 infection, which should be managed according to standard pathways. Delay or modification of therapy should be considered on an individual basis. Long‐term follow‐up studies in larger patient cohorts are required to assess the efficacy of treatment strategies employed during the pandemic.